Changes : English for international communication : workbook 1 / workbook 1 - Richards, Jack C.; Hull, Jonathan; Proctor, Susan (Cambridge :., 1994)
Where ewre you? Excuse me, I'm lost! A home of your own. I've never heard of it! Going places. Not at all! What on earth is that?...
Keywords: English language; Foreign speakers; English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; Communication, International